A Community-Engaged Approach to Select Geographic Areas for Interventions to Reduce Health Disparities - Cromley, Ellen (2011)
BACKGROUND: While neighborhood-based approaches to eliminate health disparities are on the rise, there is little guidance on how researchers may engage with community partners to select geographic areas for interventions to reduce health disparities. We aimed to identify a small geographic area to target interventions to improve diabetes-related outcomes. OBJECTIVES: We describe lessons learned from a community-engaged approach to specify the geographic area of focus. METHODS: A community-academic partnership of more than 20 organizations collaborated to develop and employ a 5-stage process to specify a target area for diabetes preventions and control activities. LESSONS LEARNED: A coalition with local knowledge and ties to the community can develop criteria and direct a process leading to selection of a geographic area, increased research capacity, and strengthened relationships among partners. CONCLUSION: A participatory approach can be effective in defining a geographic area for targeting interventions to reduce health disparities.